Transformation of Islamic Law into Positive Law within Pornography Legislation - Maulana, Rizki; Tanjung, Dhiauddin (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
As the country with the largest Muslim majority in the world, it is only natural to frame Islamic law as the legal framework for pornography legislation. The reality is that Indonesia is a unitary state, so the establishment of an Islamic state is not feasible. This article falls underthe category of literature research with a qualitative approach. The methodology used is normative legal studies with a content analysis approach. The research concludes that the transformation of Islamic legal values can be manifested in positive law by implementing Islamic law in Indonesia without establishing an Islamic state. The transformation of Islamic law into positive law in national politics regarding the Pornography Law has had a significant impact on the process of accommodating Islamic law within Indonesia's legal system. The pattern of transformation in Islamic law is substantive (essential). Although not exactly the same as what exists in the concept of Islamic law, the substance or essence is in line with Islam or not contradictory to Islamic teachings, as seen in Law No. 44 of 2008 concerning pornography.